Determination of the energy band gap of Bi2Se3 - G. Martinez (Nature Portfolio, 2017)
Abstract Despite intensive investigations of Bi2Se3 in past few years, the size and nature of the bulk energy band gap of this well-known 3D topological insulator still remain unclear. Here we report on a combined magneto-transport, photoluminescence and infrared transmission study of Bi2Se3, which unambiguously shows that the energy band gap of this material is direct and reaches E g  = (220 ± 5) meV at low temperatures.